BRModelo Web Extension: Implementing a Textual Domain-Specific Language for Conceptual Database Modeling - Ronsoni, Igor Andrey; Schreiner, Geomar A.; Duarte, Denio (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Data modeling is a fundamental step in the development of systems, as it allows domain requirements to be represented in a clear and structured manner. In the Brazilian BRModelo stands out as a widely adopted tool for creating Entity–Relationship (ER) diagrams, offering an visual interface. However, its limitation to exclusively graphical manipulation can reduce productivity and flexibility of use. This work proposes ConceptText, an extension of BRModelo WEB (BRMW) through the integration of a command-line (CMD) module with support for a dedicated textual language for the creation and manipulation of conceptual diagrams. The solution was evaluated through user experimentation, and the results indicated good acceptance, preservation of the original usability, and a perceived increase in efficiency in the modeling process. This approach contributes to its modernization and integration with contemporary development workflows.